Evolutionary history of Neotropical savannas geographically concentrates species, phylogenetic and functional diversity of lizards - Jessica Fenker; Fabricius M. C. B. Domingos; Leonardo G. Tedeschi; Dan F. Rosauer; Fernanda P. Werneck; Guarino R. Colli; Roger M. D. Ledo; Emanuel M. Fonseca; Adrian A. Garda; Derek Tucker; Jack W. Sites; Maria F. Breitman; et al. (Journal of Biogeography, 2020)
Aim Understanding where and why species diversity is geographically concentrated remains a challenge in biogeography and macroevolution. This is true for the Cerrado, the most biodiverse tropical savanna in the world, which has experienced profound biodiversity loss. Previous studies have focused on a single metric (species composition), neglecting the fact that ‘species’ within the biome are often composed of cryptic species. In order to identify biodiversity hotspots more robustly and across multiple dimensions we integrate functional, spatial and new phylogeographic data for the Cerrado lizard fauna by (a) mapping the spatial patterns of species and phylogenetic diversity; and (b) using endemism measures to identify areas of unique diversity. We then quantify the extent to which existing protected areas represent the diversity. Location Brazilian savanna (Cerrado). Methods We generated species distribution models using distribution records for all Cerrado lizard species. These, combined with mitochondrial DNA phylogenies and natural history data, allowed us to map species richness, phylogenetic and functional diversity and phylogenetic and weighted endemism. Phylogenetic endemism maps were then cross‐referenced against protected areas to calculate the amount of evolutionary history preserved within these areas. Results The central region of the Cerrado, a vast and climatically stable plateau, stands out as important under all biodiversity metrics. Including evolutionary relationships in biodiversity assessment, we detected four regional hotspots with high concentration of spatially restricted evolutionary diversity. Protected areas cover only 10% of the Cerrado area and hold 11.64% of the summed phylogenetic endemism of all lizards in the biome. Main Conclusions We highlighted both stable ( Chapada dos Veadeiros and Serra do Espinhaço plateaus) and environmentally heterogenous regions ( Araguaia and Tocantins valleys) as hotspots of evolutionary diversity. The creation and/or manipulation of areas for conservation are essential for the conservation and survival of the rich and endemic lizard fauna of the Cerrado.